2004
DOI: 10.1016/j.bbabio.2004.05.012
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of mitochondrial permeability transition induction by glycyrrhetinic acid

Abstract: Glycyrrhetinic acid (GE), the aglycone of glycyrrhizic acid, a triterpene glycoside which represents one of the main constituents of licorice root, induces an oxidative stress in liver mitochondria responsible for the induction of membrane permeability transition. In fact, GE, by interacting with the mitochondrial respiratory chain, generates hydrogen peroxide which in turn oxidizes critical thiol groups and endogenous pyridine nucleotides leading to the opening of the transition pore. Most likely the reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
45
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…in the presence of large amounts of ROS, catalase becomes the most important scavenger of H 2 O 2 in the cytosol. These conditions may be even more serious in mitochondria, as also observed in "in vitro" investigations with the organelle treated with monoamines (7), flavones (8), isoflavones (9), and cyclic triterpenes (10,11). By interacting with transition metals of the respiratory chain, these compounds produce H 2 O 2 and the highly toxic hydroxyl radical.…”
mentioning
confidence: 98%
“…in the presence of large amounts of ROS, catalase becomes the most important scavenger of H 2 O 2 in the cytosol. These conditions may be even more serious in mitochondria, as also observed in "in vitro" investigations with the organelle treated with monoamines (7), flavones (8), isoflavones (9), and cyclic triterpenes (10,11). By interacting with transition metals of the respiratory chain, these compounds produce H 2 O 2 and the highly toxic hydroxyl radical.…”
mentioning
confidence: 98%
“…Both 18␤-GA and Cbx have been shown to affect mitochondrial function by inducing the opening of the mitochondrial permeability transition pore (PTP) in rat liver mitochondria (RLM), resulting in matrix swelling, collapse of the membrane potential, and release of cytochrome c. Cyclosporine A (CsA) abolished these effects of Cbx, including reactive oxygen species (ROS) formation, indicating that Cbx induces PTP opening through the generation of oxidative stress (16,36,37). The authors suggested that the mechanism of Cbx-activated PTP opening is oxidative stress, which is produced by interacting with the mitochondrial respiratory chain at the level of complex I and complex III (36,37).…”
mentioning
confidence: 99%
“…Glycyrrhizin was shown to have anti-inflammatory properties as demonstrated by decreased production of reactive oxygen species (ROS) in human neutrophils (13). GRA can induce cell death in some tumor cells, such as primary effusion lymphoma cells transformed by Kaposi sarcoma-associated herpesvirus, possibly through the release of mitochondrial apoptotic factors (14)(15)(16). Additionally, licorice flavonoids were shown to increase the susceptibility of MRSA strains to oxacillin, a ␤-lactam antibiotic (17).…”
mentioning
confidence: 99%